How does monetary loss empathy modulate generosity in economic sharing behavior? An ERPs study. (April 2020) - Jin, Jia; Wang, Ailian; Liu, Jiaoyang; Pan, Jing; Lyu, Dong
Abstract: Previous studies have shown that generosity is driven by empathy and that both generosity in economic sharing behavior and monetary loss empathy decay as the social distance increases. However, it is still unclear whether this decay in economic sharing generosity can be influenced by the decay in monetary loss empathy. In the current study, we carried out two experiments to investigate this issue to deepen our understanding of the relationship between monetary loss empathy and generosity in economic sharing behavior. Our results show that in the observation group (observers watch their friend, and a stranger plays a gambling game), a negative correlation between log-transformed k value (ln(k)) and the distinction of d-FRN (feedback-related negativity difference between gain and loss) between friends and strangers was observed. However, in the execution group (executors play a gambling game themselves and watch a stranger play the same gambling game), there was no significant correlation between ln(k) and the distinction of d-FRN between self and strangers. Current results indicate that the decayed generosity across different social distances in economic sharing behavior can be modulated by the decayed monetary loss empathy. The study adds weight to the relationship between decayed monetary loss empathy and decayed generosity in sharing economic behavior at the level of social distance and provides electrophysiological evidence. Highlights: Individual's empathy difference affect the decay of generosity. Larger d-FRN difference elicited smaller social discounting rate. Decay of generosity is related with empathy difference rather than empathy itself. No P300 difference was found between friend's and stranger's gain and loss.